Empowering MSMEs to Independently Establish Individual Companies through Digital Government Platforms - Irma Rachmawati Maruf; Leni Widi Mulyani; Wulan Tricahyani; Alifa Nadya; Widi Restu Anengsih (LifeSciFi, 2026)
The transformation of the Micro and Small Enterprise (MSMEs) law in Indonesia has introduced Individual Companies as a simplified legal entity under the Job Creation Law. However, limited legal literacy among MSME actors remains a major obstacle to the implementation of business legalization. This Community Service activity aimed to improve participants’ understanding of business legality and the establishment process of Individual Companies. The program was conducted at NGO Kita Design Bandung and involved women-led microbusiness actors through interactive lectures, role-play simulations, practical registration tutorials, and participatory evaluations based on the Clinical Legal Education (CLE) approach. The effectiveness of the activity was measured using pre-test and post-test assessments as well as participant satisfaction evaluations. The results showed a significant improvement in participants’ understanding of the legal aspects and online registration procedures of Individual Companies. In addition, participants demonstrated high satisfaction with the training materials, facilitators, and implementation process. This activity contributes to strengthening MSMEs legal capacity, encouraging business formalization, and supporting sustainable community empowerment through practice-based legal education.